2019
DOI: 10.1088/2051-672x/ab4cc6
|View full text |Cite
|
Sign up to set email alerts
|

3D optical surface profiler for quantifying leaf surface roughness

Abstract: Biological efficiency of pesticide droplets is affected by leaf surface fine structures; however, few reliable methods exist to physically measure and quantify surface roughness. A 3D optical surface profiler was evaluated for its effectiveness as a novel and reliable method to measure and quantify leaf surface roughness in terms of areal roughness parameters. Evaluations included its accuracy for measuring 3D roughness parameters relating mean roughness length, S a , skewness, S sk , and kurtosis, S ku . Thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…A 50× Nikon Mirau interferometric objective lens was used to determine the surface profile of the plates. The S q roughness was defined as [ 70 ]: …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 50× Nikon Mirau interferometric objective lens was used to determine the surface profile of the plates. The S q roughness was defined as [ 70 ]: …”
Section: Discussionmentioning
confidence: 99%
“…The Sq roughness was defined as [65]: 𝑆 𝑞 = √ 1 𝐴 ∬ 𝑍 2 (𝑥, 𝑦) 𝑑𝑥 𝑑𝑦 𝐴 . Here, A is the area and Z(x,y)…”
Section: Methodsmentioning
confidence: 99%
“…Cells apical surfaces can be smooth ( Figures 1 A and 1B) or decorated with minute structures (such as striations seen in Figure 1 D) that must be accounted for to understand epidermis properties. By deploying a 3D surface profiler to quantify precisely leaf roughness in various species, a team of engineers showed that the ability of leaves to wet is highly dependent on the height and relative spacing between the micro/nanofeatures that generate the coarseness ( Abbott and Zhu, 2019 ). Similarly, measuring accurately the geometry of conical cells from flowers displaying UV-absorbing and UV-reflecting sectors revealed that the UV-absorbing regions tend to have higher, more acute, cellular profiles.…”
Section: Structural Patterns: Diversity Overview and Biological Functionsmentioning
confidence: 99%
“…In the manufacturing industry, surface roughness characterization is standardized, whereas, unfortunately, a mature method for surface roughness characterization of leaves is lacking [5]. Pioneers of the field attempted to account for contact angle as a parameter in roughness coefficient [6,7] by contrasting the contact angle of rough surfaces with that of smooth surfaces, where the roughness coefficient is merely a relative and indirect assessment of roughness.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, AFM can only gain access to onedimensional profile within an action cycle, and its z-range for leaves of many plant species is unacceptably narrow. Optical profiler, a profiler based on optical principles such as phase shifting interferometry, was used to render the surface of plant leaves [5,15]. Using interferometry, speckles formed by white light interferer compose optical sections, and then the leaf surface can be reconstructed from these sections.…”
Section: Introductionmentioning
confidence: 99%